Effect of pH on COD Reduction in Biogas Formation - Nadiareta Sitorus; Desniorita Desniorita (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Biogas is a mixture of gases formed from the decomposition of organic materials with the help of bacteria through an anaerobic fermentation process (airtight) to produce biogas in the form of methane gas (CH4) that can be managed. In biogas production, pH is one of the factors that affects the production process where an inappropriate pH will cause the performance of microorganisms in degrading organic matter into biogas to be less than optimal. This can be seen from the COD reduction produced, namely COD reduction will increase when operating conditions are at optimal pH, for this reason, conditioning the operating process according to the optimum pH is needed. So that in order to maximize the production of biogas produced, research was conducted to determine the optimum pH in the biogas production process carried out at PT AMP Plantation. In this study, biogas production data was collected so that the optimum pH in the production process carried out was known. From the research that has been carried out, the optimum pH for the biogas production process is 7, which produces the highest COD reduction of 91.78%.